Electronically captured, patient‐reported physical function: an important vital sign in obesity medicine. (20th September 2016) - Fleming, J.; Wood, G. C.; Seiler, C.; Cook, A.; Lent, M. R.; Still, C. D.; Benotti, P. N.; Irving, B. A.
Summary: Objectives: Impaired physical function (i.e., inability to walk 200 feet, climb a flight of stairs or perform activities of daily living) predicts poor clinical outcomes and adversely impacts medical and surgical weight management. However, routine assessment physical function is seldom performed clinically. The PROMIS Physical Function Short Form 20a (SF‐20a) is a validated questionnaire for assessing patient reported physical function, which includes published T‐score percentiles adjusted for gender, age and education. However, the effect that increasing levels of obesity has on these percentiles is unclear. We hypothesized that physical function would decline with increasing level of obesity independent of gender, age, education and comorbidity. Materials and Methods: This study included 1, 627 consecutive weight management patients [(mean ± SEM), 44.7 ± 0.3 years and 45.1 ± 0.2 kg/m 2 ] that completed the PROMIS SF‐20a during their initial consultation. We evaluated the association between obesity level and PROMIS T‐score percentiles using multiple linear regression adjusting for gender, age, education and Charlson Comorbidity Index (CCI). Results: Multiple linear regression T‐score percentiles were lower in obesity class 2 (−12.4%tile, p  < 0.0001), class 3 (−17.0%tile, p  < 0.0001) and super obesity (−25.1%tile, p  < 0.0001) compared to class 1 obesity. Conclusion: In patients referred for weight management, patient reported physical function was progressively lower in a dose‐dependent fashion with increasing levels of obesity, independent of gender, age, education and CCI.